Fleabrain loves Franny - Rocklin, Joanne (Amulet Books, 2014)
This gem of a novel takes place in Pittsburgh in 1952. Franny Katzenback, while recovering from polio, reads and falls in love with the brand-new book Charlotte’s Web. Bored and lonely and yearning for a Charlotte of her own, Franny starts up a correspondence with an eloquent flea named Fleabrain who lives on her dog’s tail. While Franny struggles with physical therapy and feeling left out of her formerly active neighborhood life, Fleabrain is there to take her on adventures based on his extensive reading. It’s a touching, funny story set in the recent past, told with Rocklin’s signature wit and thoughtfulness